Lignin degradation and stability: Volatile Organic Compounds (VOCs) analysis throughout processing. (August 2016) - Sallem-Idrissi, Naïma; Vanderghem, Caroline; Pacary, Tiphanie; Richel, Aurore; Debecker, Damien P.; Devaux, Jacques; Sclavons, Michel
Abstract: This work investigates the Volatile Organic Compounds (VOCs) emissions during the processing of composite of polyamide 6 (PA) bio-filled with technical lignin. This is of prime interest as volatile phenolic structural monomers issued from lignin could penetrate the human organism and cause undesirable health damages. A special attention is given to the measurement of formaldehyde as it is known to be a human carcinogen. Lignin main identified emission consists of a high level of formaldehyde and a large amount of complex substituted phenol and benzene, all representative and constitutive of its structure. Regarding the PA alone, it has been found that the predominant VOC product is ε-caprolactam. When filling PA6 with lignin, the emitted VOCs associated to this filler are mainly produced during the extrusion while, only traces are detected during the injection process. Formaldehyde emission level is three times higher during the injection than during the extrusion. Phenols and some remaining reactants used during industrial cellulosic extraction process are identified. Regarding the value of the Short-Term Exposure Limit (STEL), suitable industrial process, safety and hygiene rules must be adopted.